Pergeseran Penerjemahan Tarkib Idafi dalam Terjemehan Novel Karya Najib Kailani “Layali Turkistan” - Merry Choironi; Azzahra Mumtazah (Alfaz (Arabic Literatures for Academic Zealots), 2018)
There frequently un-correspondences of word level, word unit, structure, and intra system in translation activities between those of the source language and those of the target language. This so-called shift of translation may also occur on the level of meaning, be it to the more specific meaning, to the more general meaning, or simply as the result of different nature between two languages. This phenomenon was also found by the researchers in the novel entitled “Para MujahidCinta” whichis the translated version from the Arabic of one of the most Egyptians best novelist Najīb Kīlānī, entitled Layālī Turkistān. The results of the research show that the translator, Shocheh Muhammad, employed such shift in his translation particularly in regards with the tarkīb iḍāfī, composite words with a solid meaning, to become reduced-adjective clause, reduced-adverb clause, or etcetera. Such changes in translation affirm that shifts may occur, not only by the need to deliver the meaning or message, but also –in a wider context- by the fact of different characteristics of languages. This is, to some extent, nothing to do with correspondence between two languages which is the basis of translation theories.